INTERNALLY DISPLACED PERSONS (IDPs) IN NIGERIA: THE ROLES OF INTERNATIONAL ACTORS - TASIU MAGAJI (International Studies Journal)
The paper examines the global responsibility to protect internally displaced persons (IDPs) in Nigeria. It utilizes case studies, reports, and official documents to assess the current response to internal displacement in Nigeria and identify its challenges and shortcomings. The paper argues that the needs of IDPs in Nigeria have not been adequately addressed due to factors such as a lack of political will, limited resources, and structural barriers stemming from government corruption and conflict dynamics. Additionally, the study analyzes the roles and responsibilities of international actors, including the United Nations and international NGOs, in providing assistance to IDPs. It asserts that although these actors have made some progress in addressing the issues faced by IDPs in Nigeria. However, more effort is required to ensure the protection of their rights and reintegration into their communities. In conclusion, the paper calls for a more coordinated and comprehensive approach to the protection of IDPs in Nigeria, as well as the fulfillment of international obligations to assist them in achieving sustainable solutions.